STEROIDAL SAPOGENINS 170 THE POSITION OF THE DOUBLE BOND IN YUCCAGENIN AND KAMMOGENIN - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
The double bond in kammogenin and yuccagenin has been shown to be in the 5,6-position in the molecule.
J PHYS SOC JPN
Keywords: STEROIDAL SAPOGENINS. 170., POSITION, DOUBLE BOND, YUCCAGENIN, KAMMOGENIN; QUIMICA; QUIMICA FISICA; QUIMICA AMBIENTAL